Thrombin Activatable Fibrinolysis inhibitor Thr 325 Ile polymorphism in fetuses with factor XIII deficient family history and Intracranial hemorrhage - naderi, majid; esmaeili reykande, samira; dorgalaleh, akbar; alizadeh, shaban; abtahi, zahrasadat (Archives of Medical Laboratory Sciences, 2019)
Background: Factor XIII Deficiency (FXIIID) is an inherited rare bleeding disorder with some life threatening clinical manifestation including Intracranial Haemorrhage (ICH). Among all polymorphisms found in FXIIID, Thrombin Activatable Fibrinolysis Inhibitor (TAFI) Thr325Ile gene polymorphism increases probability of ICH about 20 fold in patients with FXIII .So, in this study we aimed to evaluate TAFI Thr 325 Ile polymorphism in Chorionic villus samples (CVS) of fetuses with positive family history of FXIIID and ICH. Materials and Methods: This study was performed on chorionic villus of pregnant mothers ´ with positive history of FXIIID accompanied with ICH in first-degree relatives of their fetus. All parents of the fetuses were completed consent form for doing Prenatal diagnosis (PND). Chorionic villus DNA was extracted from each sample using the DNA extraction kit and PCR-RFLP was performed for TAFI Thr 325Ile polymorphism in Exon 4 of FXIII A gene. Results: All of 8 fetuses had positive family history of FXIIID. Seven out of eight fetuses (87.5%) had a family member with CNS bleeding due to FXIIID. Four fetuses had history of death due to FXIIID. There were 5 case (62.5%) that were homozygote for TAFI Thr 325 Ile, one (12.5%) was heterozygote and two (25%) were non mutant. Conclusion: Detection of TAFI Thr 325 Ile polymorphism by PND program in fetuses with positive family history of ICH is seems necessary and it will help to fill many gaps in preventing life threatening features of FXIIID in newborn at the time of delivery by prophilaxy receiving and precautionary measures.